PERAN PENDIDIK DALAM PENGEMBANGAN DIRI PESERTA DIDIK di MTs AS’ADIYAH KECAMATAN SAMBOJA KAB. KUTAI KARTANEGARA - Anggranti, Wiwik (Al Tadib : Jurnal Ilmu Pendidikan, 2015)
This study examines the role of educators incasuistry in the development of self-learners. Plus selfimprovementis the ability of learners in completecompetence in curriculum demands. The purpose of thisstudy was to determine and describe the role of educatorsin the development of self-learners in the DistrictAs'adiyah MTs Samboja Kab. Kutai. With the modelqualitative descriptive study, researchers sought toexplore the field data as observers. The results showedthat the role of educators as informator, motivator,organizer, director, initiator, transmitter, facilitators,mediators, evaluators quite familiar with their duties andcarry out the task with the facilities and infrastructure thatexist and the role of educators in the development of selflearnersis very central though with facilities andinfrastructure is very limited.Keywords: self-development, the role and duties ofteachers